2003
DOI: 10.1148/radiol.2281020489
|View full text |Cite
|
Sign up to set email alerts
|

Mammography with Computer-aided Detection: Reproducibility Assessment—Initial Experience

Abstract: Reproducibility of marked regions generated by the CAD system is improved from that reported previously, largely as a result of the substantial reduction in the false-positive detection rates. Reproducibility of true-positive identification of masses remains an important issue that may have methodologic and clinical practice implications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
23
0
1

Year Published

2005
2005
2015
2015

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(27 citation statements)
references
References 14 publications
3
23
0
1
Order By: Relevance
“…30 Zheng and coworkers reported that the sensitivity for the detection of clustered microcalcifications is high at 96% but that sensitivity for mass is only 66.7% to 70.8%. 31 The authors also noted that the abnormalities in their study were visible on both views and that they were not particularly subtle. Further improvements must be achieved in the detection of masses for CAD systems to be sufficiently reliable for general use, and for the possibility of achieving the increased sensitivity of a second reader.…”
Section: How Frequently Are Breast Cancers Missed By Mammography?mentioning
confidence: 77%
“…30 Zheng and coworkers reported that the sensitivity for the detection of clustered microcalcifications is high at 96% but that sensitivity for mass is only 66.7% to 70.8%. 31 The authors also noted that the abnormalities in their study were visible on both views and that they were not particularly subtle. Further improvements must be achieved in the detection of masses for CAD systems to be sufficiently reliable for general use, and for the possibility of achieving the increased sensitivity of a second reader.…”
Section: How Frequently Are Breast Cancers Missed By Mammography?mentioning
confidence: 77%
“…Their results are not akin to ours (100% for malignant calcifications, 85% for high-risk calcifications and 61% for benign calcifications) and this may represent the differences from using direct (our study) vs indirect CAD (with digitisation of images) systems. In the field of CAD, the issue of reliability and reproducibility, which has been shown to be far from perfect in screen-film mammography (SFM) [2,13,14] as a result of mechanical scanning, virtually does not exist in FFDM since the mechanical process of scanning is avoided and CAD software is directly applied to the digital mammogram. Amorphous calcifications are frequently overlooked on SFM and can contribute to a substantial number of missed carcinomas [9,12,15,16].…”
Section: Discussionmentioning
confidence: 99%
“…Computer-aided detection (CAD) systems help radiologists with the perception of the cancer, marking regions of interest on the screen. The use of CAD software primarily in full-field digital mammography (FFDM), also known as direct CAD (d-CAD), does not require digitisation of the films and by definition, once an image is acquired, the CAD detection result will be reproducible when the same d-CAD scheme is applied repeatedly to such an image [2].…”
mentioning
confidence: 99%
“…Contradicting these unpublished data of the companies, it is now well accepted that the reproducibility of CAD systems with a secondary digitization of conventional images is limited by its nature. The first study describing this lack of technology was published by Malich et al in 2000; other studies have supported these findings [74][75][76].…”
Section: Reliabilitymentioning
confidence: 90%